Characterization of FKGK18 as Inhibitor of Group VIA Ca2+-Independent Phospholipase A2: Candidate Drug for Preventing Beta-Cell Apoptosis and Diabetes - Ali, Tomader; Kokotos, George; Magrioti, Victoria; Bone, Robert N.; Mobley, James A.; Hancock, William; Ramanadham, Sasanka (PLoS ONE, 2013)
Ongoing studies suggest an important role for iPLA2β in a multitude of biological processes and it has been implicated in neurodegenerative, skeletal and vascular smooth muscle disorders, bone formation, and cardiac arrhythmias. Thus, identifying an iPLA2β inhibitor that can be reliably and safely used in vivo is warranted. Currently, the mechanism-based inhibitor bromoenol lactone (BEL) is the most widely used to discern the role of iPLA2β in biological processes. While BEL is recognized as a more potent inhibitor of iPLA2 than of cPLA2 or sPLA2, leading to its designation as a “specific” inhibitor of iPLA2, it has been shown to also inhibit non-PLA2 enzymes. A potential complication of its use is that while the S and R enantiomers of BEL exhibit preference for cytosol-associated iPLA2β and membrane-associated iPLA2γ, respectively, the selectivity is only 10-fold for both. In addition, BEL is unstable in solution, promotes irreversible inhibition, and may be cytotoxic, making BEL not amenable for in vivo use. Recently, a fluoroketone (FK)-based compound (FKGK18) was described as a potent inhibitor of iPLA2β. Here we characterized its inhibitory profile in beta-cells and find that FKGK18: (a) inhibits iPLA2β with a greater potency (100-fold) than iPLA2γ, (b) inhibition of iPLA2β is reversible, (c) is an ineffective inhibitor of α-chymotrypsin, and (d) inhibits previously described outcomes of iPLA2β activation including (i) glucose-stimulated insulin secretion, (ii) arachidonic acid hydrolysis; as reflected by PGE2 release from human islets, (iii) ER stress-induced neutral sphingomyelinase 2 expression, and (iv) ER stress-induced beta-cell apoptosis. These findings suggest that FKGK18 is similar to BEL in its ability to inhibit iPLA2β. Because, in contrast to BEL, it is reversible and not a non-specific inhibitor of proteases, it is suggested that FKGK18 is more ideal for ex vivo and in vivo assessments of iPLA2β role in biological functions.